Aqueous Zn-ion batteries using amorphous Zn-buserite with high activity and stability - Wang, Zhi-Qiang; Liu, Xiao-Dong; Chen, Hong-Ming; Zhu, Xiang-Yu; Song, Li-Ying; Yang, Yun-Guo; Bai, Jing; Kim, M. J; Lau, Woon-Ming; Rosei, Federico; Zhou, Dan (Journal of materials chemistry. A, Materials for energy and sustainability, 2023)
Amorphous manganese oxides (a-MnO x ) are widely considered promising material systems to fabricate cathodes for aqueous zinc ion batteries (AZIBs). However, the Zn-storage mechanism of a-MnO x is still not understood, and its electrochemical performance is inadequate. Herein, we report porous reduced graphene oxide boosted a-MnO x microspheres (denoted as PrGO-MnO x ) as a cathode material for AZIBs. Its electrochemical Zn-storage mechanism was elucidated via a series of ex situ measurements. Particularly, we observe that the a-MnO x phase in PrGO-MnO x is transformed into highly active and stable amorphous Zn-buserite during the initial cycles, effectively promoting Zn-storage. The cathode material can deliver a large capacity (296 mA h g −1 after 100 cycles at 0.1 A g −1 ), high-rate capability (151 mA h g −1 at 2.5 A g −1 ), and ultra-long lifespan (5000 cycles at 5.0 A g −1 ). We attribute this performance to several properties, including (i) the amorphous structure of Zn-buserite with high activity and stability, (ii) fast reaction kinetics, (iii) increased electron conductivity, (iv) improved Zn 2+ diffusion rate, and (v) high pseudocapacitance. We also assembled a PrGO-MnO x |AQ (9,10-anthraquinone) full-battery, which possesses a high discharge plateau (0.8 V) and impressive cycling stability (106 mA h g −1 after 500 cycles at 0.3 A g −1 ), indicating good potential towards practical applications. Herein, a novel PrGO-MnO x microsphere cathode material is developed for aqueous zinc ion batteries. It reveals the phase transformation of a-MnO x into highly active amorphous Zn-buserite upon the initial cycles, enabling excellent Zn-storage.